Penerapan Scoring System Dalam Penilaian Latihan Pemahaman Materi Toefl - Azharuddin, Muhammad (TIN: Terapan Informatika Nusantara, 2020)
Nowadays, computer skills can be used in various fields to teach, provide information, and provide entertainment. Computers can also be used to assist in the teaching and learning process. To facilitate the delivery of material, it can be packaged attractively in the form of an Android-based application, which is educational and entertaining for students. The topic of this discussion is the design of the toefl understanding training application using the Android-based scoring system method. Where to use this application can help students in learning computerized toefl material. Therefore the authors apply the scoring system method to determine the scores and categories in the toefl assessment, there are three categories, namely less good, good and very good. The purpose of this study was to design an Android-based toefl material application, where the training scores were implemented using the scoring system method. This application will make it easier for students to learn toefl, because the application system is already in the form of android so that it adds to the attractiveness of students.